MELLOM SNORRES KONGESAGAER OG JOIKENS RYTME. OM BEAIVVÁŠ SÁMI NAŠUNÁLATEÁHTERS "SNØFRID" (2018) - SIBINSKA, Maria (Studia Universitatis Babeș-Bolyai Philologia, 2020)
Between Snorre's King Sagas and the rhythm of the joik: On The Sami National Theatre's Snøfrid (2018). “Beaivváš” is a Sami theatre having the status of a national theatrical institution in Norway. In 2021 it celebrates its 40th anniversary. The article focuses on the performance of Snøfrid which was staged by the Sami National Theatre in 2018. The performance is based on the story about the marriage between King Harald Fine-Hair and a young Sami woman. The story is known thanks to Snorri Sturlason. His Heimskringla was instrumental in forming ideas concerning the founding of the Kingdom of Norway and became a significant point of reference for the definition of Norwegian national identity in the 1800's. The author of the article wishes to show the dual function of the performance: both as a correction of preconceptions of minority culture and as an expansion of the discourse on the state and nation of Norway. Snøfrid is interpreted from a postnationalistic perspective and viewed as a correcting voice compared to the mythology of national unification, and it is emphasized that the corrective voice of the performance is not a critique of Norse narrative tradition; rather, it is a critique of the 19th century version of that tradition. The author of the article identifies the individualization of the main character as the correcting strategy of the performance. The article throws light on those selective elements of performance aesthetics that contribute to the process of individualization. REZUMAT. Între scrierile saga despre regi ale lui Snorri Sturlason și ritmul joik-ului: despre spectacolul Snøfrid al Teatrului Național Lapon (2018). „Beaivváš” este un teatru lapon având statutul de instituție teatrală națională în Norvegia. În 2021 sărbătorește 40 de ani de la înființare. Articolul se concentrează pe spectacolul Snøfrid, care a fost pus în scenă de Teatrul Național Lapon în 2018. Spectacolul se bazează pe povestea despre căsătoria dintre regele Harald Hårfagre (Harald cu Păr Frumos) și o tânără laponă. Povestea este cunoscută datorită lui Snorri Sturlason. Scrierea sa, Heimskringla, a contribuit la formarea ideilor privind fondarea Regatului Norvegiei fiind un punct de referință pentru definirea identității naționale norvegiene în anii 1800. Autorul articolului dorește să arate dublă funcție a spectacolului: atât ca o corecție a preconcepțiilor despre cultura minorității, cât și ca o extindere a discursului asupra statului și națiunii Norvegiei. Spectacolul Snøfrid este interpretat dintr-o perspectivă post-naționalistă și privit ca o voce corectivă la mitologia unificării naționale, arătând că vocea corectivă a spectacolului nu este nicidecum o critică adusă tradiției narative norvegiene; ci mai degrabă, este o critică a versiunii secolului XIX a acestei tradiții. Autorul articolului identifică individualizarea personajului principal ca strategie de corectare a spectacolului. Articolul aruncă lumină asupra acelor elemente selective ale esteticii teatrale care contribuie la procesul de individualizare. Cuvinte cheie: Teatrul lapon Beaivváš, literatura norvegiană veche, unificarea Norvegiei, discursul post-naționalist, cultura laponă.